Contribution of Cash Waqf in Improving Programs in the Field of Education (Study at International Islamic University (IIUM Endowment Fund) Malaysia) - Arifani, Devina; Victoria, Ong Argo; Rozihan, Rozihan (LAW FACULTY UNISSULA, 2024)
Waqf is a kind of charity whose rewards will flow even if the person who fulfills it has died. The benefits of the donated assets will still benefit the wider community, even if the waqif has died. When waqf is in the form of land and buildings, now you can donate online. Online waqf is a way of giving waqf by utilizing technology and the internet. The type given is cash waqf in the form of funds collected to build various public facilities and places of worship. Later, the funds that have been collected will be used to be distributed to charity projects and social activities that provide long-term benefits for the wider community, such as building mosques, orphanages, schools, hospitals, and so on. Distribution can be done on platforms that provide waqf facilities with payment methods via electronic transfer or online payment. So what is the law on online waqf? Most scholars believe the law is permissible. This is because in waqf, consent does not always have to be done directly. This means that the waqf remains valid, whether the consent and qabul are carried out face to face between the waqif and the nadzhir (waqf manager), or not in person. Most importantly, waqf must have a written agreement so as not to cause problems in the future. This is because waqf is long-term, even until the waqif dies. The waqf method is carried out by transferring a certain amount of funds to the waqf manager. After waqf, you will receive written evidence in the form of a waqf certificate issued by the waqf institution. Online waqf is one way of giving waqf that makes it easy for waqifs and nadzhir. Transactions can be done quickly without having to visit the waqf institution. As a result, digital waqf is said to be very economical in terms of costs and time. Apart from that, there are several advantages of doing online waqf, including: Wider Reach, More Efficient and Transparent, Ease of Choosing Waqf Programs and Wider Distribution.